If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -3)(x + -1) = 6 + 2(x + 2)(x + 3) Reorder the terms: (-3 + 2x)(x + -1) = 6 + 2(x + 2)(x + 3) Reorder the terms: (-3 + 2x)(-1 + x) = 6 + 2(x + 2)(x + 3) Multiply (-3 + 2x) * (-1 + x) (-3(-1 + x) + 2x * (-1 + x)) = 6 + 2(x + 2)(x + 3) ((-1 * -3 + x * -3) + 2x * (-1 + x)) = 6 + 2(x + 2)(x + 3) ((3 + -3x) + 2x * (-1 + x)) = 6 + 2(x + 2)(x + 3) (3 + -3x + (-1 * 2x + x * 2x)) = 6 + 2(x + 2)(x + 3) (3 + -3x + (-2x + 2x2)) = 6 + 2(x + 2)(x + 3) Combine like terms: -3x + -2x = -5x (3 + -5x + 2x2) = 6 + 2(x + 2)(x + 3) Reorder the terms: 3 + -5x + 2x2 = 6 + 2(2 + x)(x + 3) Reorder the terms: 3 + -5x + 2x2 = 6 + 2(2 + x)(3 + x) Multiply (2 + x) * (3 + x) 3 + -5x + 2x2 = 6 + 2(2(3 + x) + x(3 + x)) 3 + -5x + 2x2 = 6 + 2((3 * 2 + x * 2) + x(3 + x)) 3 + -5x + 2x2 = 6 + 2((6 + 2x) + x(3 + x)) 3 + -5x + 2x2 = 6 + 2(6 + 2x + (3 * x + x * x)) 3 + -5x + 2x2 = 6 + 2(6 + 2x + (3x + x2)) Combine like terms: 2x + 3x = 5x 3 + -5x + 2x2 = 6 + 2(6 + 5x + x2) 3 + -5x + 2x2 = 6 + (6 * 2 + 5x * 2 + x2 * 2) 3 + -5x + 2x2 = 6 + (12 + 10x + 2x2) Combine like terms: 6 + 12 = 18 3 + -5x + 2x2 = 18 + 10x + 2x2 Add '-2x2' to each side of the equation. 3 + -5x + 2x2 + -2x2 = 18 + 10x + 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 3 + -5x + 0 = 18 + 10x + 2x2 + -2x2 3 + -5x = 18 + 10x + 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 3 + -5x = 18 + 10x + 0 3 + -5x = 18 + 10x Solving 3 + -5x = 18 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 3 + -5x + -10x = 18 + 10x + -10x Combine like terms: -5x + -10x = -15x 3 + -15x = 18 + 10x + -10x Combine like terms: 10x + -10x = 0 3 + -15x = 18 + 0 3 + -15x = 18 Add '-3' to each side of the equation. 3 + -3 + -15x = 18 + -3 Combine like terms: 3 + -3 = 0 0 + -15x = 18 + -3 -15x = 18 + -3 Combine like terms: 18 + -3 = 15 -15x = 15 Divide each side by '-15'. x = -1 Simplifying x = -1
| 3/21,1/15 | | x(5)=23 | | 9y-24=-3(-3y+8) | | 5x+3x=48 | | 18.4/2.3 | | 7(x-1)-3(2x+1)=0 | | 329.5/28.4 | | x^2+8x-128=0 | | 329.44/28.4 | | 7+3c-5-6c= | | 72/127+2/3 | | (10)x=6 | | 2x^2+7x-x^2+4=1 | | 6x^2+72x=-192 | | 7-6-2c+9c= | | 2r+6t= | | 5(7+p)=30 | | -7(3x+6)=-84 | | 4x^2-48x+128=0 | | 6x-8=16+10 | | -2(x-1)=3x-18 | | 7+8n+5-3n= | | 3x-19=7x+17 | | 38+x+90=180 | | 2.3/18.4 | | 3(2+3K)+4(X-2)=5 | | 42=4y-14 | | 37+x+90=180 | | 30(10x-2)+x=56 | | -4z-2+8+5z= | | 86-x=266 | | 4(2x-3)+6=18 |